The Influence of Transformational Leadership on Organizational Commitment and Job Satisfaction with Procedural Justice as Mediating Variable - Rico Saktiawan Jaya (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2018)
The purpose of this research is to test the influence of transformational leadership on organizational commitment and job satisfaction with procedural justice as mediating variable. The role of the leader is very important given the nature of the leadership taken by these leaders can exert influence on employee commitment and job satisfaction, building on the principles of justice. This study uses a quantitative approach using a survey method and questionnaire instruments. Sampling of this research using purposive sampling that employees who have worked at least two years and subordinate superintendent in Coal and Processing Handling Division (CPHD) PT KPC. Hypothesis testing is conducted using hierarchical regression methods to test mediation in accordance with the rules of Baron and Kenny (1986). Questionnaire data processing taken by SPSS Statistics 21. The results of this study indicate that procedural justice is partially mediates the influence of transformational leadership on organizational commitment and job satisfaction.